Comparison of Metabolite Changes in Lycium barbarum Bud Tea at Different Processing Stages by Widely Targeted Metabolomics - WEI Jiayi, MI Jia, ZHANG Bo, WANG Siyu, GE Xinyu, JIN Bo, LUO Qing, ZHANG Lutao, LU Lu, YAN Yamei (Shipin Kexue)
In this study, the changes in total polyphenols, total flavonoids and chlorogenic acid contents during the processing of Lycium barbarum bud tea were compared and analyzed, and the metabolite composition of the tea at different processing stages was systematically analyzed by widely targeted metabolomics to clarify their effects on the chemical composition of L. barbarum bud tea. The results showed that L. barbarum buds had the highest contents of total polyphenols, (43.65 ± 3.15) mg/g, total flavonoids, (10.68 ± 0.25) mg/g, and chlorogenic acid (5.24 ± 0.52) mg/g. The contents of these phenolic substances decreased significantly (P < 0.05) as bleaching, primary fixation, secondary fixation, frying and flavoring progressed. Notably, after the secondary fixation, the contents of total polyphenols, total flavonoids and chlorogenic acid decreased by 19%, 29% and 27%, respectively. Widely targeted metabolomics identified 594 metabolites belonging to 11 categories, including flavonoids, phenolic acids, alkaloids, amino acids and their derivatives, and lipids. In total, 270, 287, 298, 295, and 298 significantly differential metabolites were identified in L. barbarum buds versus bleaching, primary fixation, secondary fixation, frying and flavoring, respectively, with the major ones being flavonoids, nucleotides and their derivatives, phenolic acid, amino acids and their derivatives. These differential metabolites were predominantly enriched in metabolic pathways such as purine metabolism, niacin and nicotinamide metabolism, cysteine and methionine metabolism, and a small proportion of them was enriched in pathways like zeeatin biosynthesis, and ABC transporter. Significant differences were observed in inosine, homocysteine, cinnamic acid, 4-hydroxy-3-methoxycinnamic acid, and isoferulic acid among processing stages, indicating their involvement in the quality formation of L. barbarum bud tea during processing. The findings of this study provide a theoretical basis for understanding the changes in nutritional and functional components and for the quality control of L. barbarum bud tea during processing.